The Effect of Entrepreneurial Orientation on the Performance of MSME Craftsmen Supporting Cultural Events Mediated by Innovation Capacity - Andi Hasbi; Dharma Kuba; Nur Farah Fajriaty Muchlis (Borong Newinera Publisher, 2023)
The aim of the research is to find out Entrepreneurial Orientation on the Performance of MSME Craftsmen Supporting Cultural Events Mediated by Innovation Capacity. This research uses quantitative methods using survey methods. This research was conducted in Soppeng, Wajo and Bone Regencies. The data analysis technique used in this research is Partial Least Square (PLS) regression analysis. The results of the research show that the results of the inner model evaluation of Entrepreneurial orientation on MSME Performance are mediated by Innovation Capacity, resulting in a statistical P value of 2.517 or greater than 1.96 and a P value of 0.012 or smaller than 0.67, so this hypothesis declared accepted. The results of hypothesis testing state that entrepreneurial orientation has a positive effect on MSME performance which is mediated by Innovation Capacity.